Pengaruh Influencer Marketing dan Online Customer Review terhadap Keputusan Pembelian produk Fashion melalui Marketplace Shopee - Wahyudi, Agung Tri; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
Online shopping has become a trend among young people today, the use of influencers to promote products is increasing as millennials are becoming more active on social media. Millennials are increasing their access to social media so they spend a lot of time and enjoy interesting content from influencers. The phenomenon of the rapid growth of influencer marketing is one of the marketing strategies that are quite effective in influencing consumers to buy. On the other hand, consumers who want to buy online tend to be more critical and careful in choosing the goods to be purchased, this is because buyers cannot directly see or touch the products they will buy. With this, online customer reviews are also an important factor in shaping consumer perceptions of the assessment of a product. This study uses a quantitative method using an online questionnaire method through Google Forms as a data collection tool. The research sample consists of Shopee consumers who have purchased fashion products through the Shopee Marketplace. Data analysis was processed using multiple linear regression analysis and continued with the classical assumption test and then ended by testing the research hypothesis. The results obtained from the data origin test in this study prove that influencer marketing and online customer reviews have a significant influence on purchasing decisions.